Health Promotion Behaviors and Association with Some Variables for Clients with Type II Diabetes Mellitus at Al-Hassan Diabetes and Endocrine Center - Sabah Jaryan, Fatima; Abdul Hussein Al-Abedi, Ghazwan (Kerbala Journal of Nursing and Health Sciences., 2025)
Background: Those with Type 2 Diabetes Mellitus (T2DM) who participate in harmful behaviors are at an elevated risk for experiencing a range of adverse health outcomes. Methods: The study focused on clients diagnosed with T2DM at Al-Hassan Diabetes. A Health Promotion Behaviors HPLP-ll and Demographic Questionnaire was utilized, and regression logistical was employed to examine the connection that exists between health promotion behaviors and the identified demographic variables. A significant negative correlation was observed between health promotion behaviors and the variables of age, occupation, and monthly income. In contrast, a significant positive correlation was identified between health promotion behaviors and educational level among clients with T2DM, as indicated by the Pearson correlation coefficient. However, no significant relationships were found between marital status, residency, and health promotion behaviors. Conclusion: this study highlights that health promotion behaviors in individuals with Type 2 Diabetes Mellitus are influenced by age, occupation, monthly income, and educational level. A negative correlation was found with age, occupation, and income, while a positive correlation was observed with education. These findings suggest the need for tailored interventions based on demographic factors to improve diabetes management.